AN ANALYSIS OF IDEATIONAL MEANING REALIZED ON RECOUNT TEXTS IN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL GRADE X - Eros Cahyati (JALL (Journal of Applied Linguistics and Literacy), 2019)
This research is aimed at analyzing the ideational meaning realized on recount texts in English textbook for Senior High School Grade X.  The objectives of this study are to describe the dominant processes and circumstances realized on recount texts in English textbook. The researcher employed qualitative descriptive as the research design.  The data were taken and collected through a documents collection.  The documents were collected from English textbook for Senior High School Students Year X (revised 2017). This book was published by Pusat Kurikulum and Perbukuan, Balitbang, Kemendikbud (2017). There were 4 recount texts that analyzed and identified. The researcher used transitivity analysis as tool to analyzes recount texts. The results of data analysis showed that the dominant processes found on recount texts is material processes. It   occurred 90 times (51.8%) in the textbook and it refers to process of construing material of action and doing. Meanwhile, the dominant circumstances found on recount texts is circumstances of time. It is occurred 40 times (44.4%) and it refers to answer question such as “when?” and also to give information about times. Finally, this research is recommended for the students of English education program who want to improve their understanding about SFL especially in ideational meaning. Keywords: Ideational meaning, recount texts, textbook